The milk fermented with Lactobacillus fermentum ameliorates indomethacin-induced intestinal inflammation: An exploratory study - Santiago-Lopez, Lourdes (2019)
The aim of this study was to evaluate the e ect of milk fermented with Lactobacillus fermentum J20 (FMJ20) or J28 (FMJ28) on ameliorating indomethacin-induced inflammation. Twenty-eight male C57Bl/6 mice were divided into four experimental groups: indomethacin, indomethacin + FMJ20, indomethacin + FMJ28, and untreated (control). Groups were fed fermented milk for 15 days, followed by administration of indomethacin supplied in three sub-doses over experimental period. Body weight, and food consumption were recorded. Additionally, spleen, kidney, and liver were weighed, and the small intestine length was measured. The cytokines in serum (IL-2, IL-4, IL-6, IL-10,IL-17, IL-23 and TNF ) and in intestinal mucosa (IL-17 and IFN) were also determined. Compared to the control, all indomethacin-supplemented groups lost weight (~2.7 g; p < 0.05), but no changes were found in the organ-specific morphometry analysis. FMJ28 showed better results in attenuating serum and intestinal IL-17 levels. Furthermore, showed less epithelial cell loss and inflammatory infiltrates than the other indomethacin-treated groups. These results suggest that FMJ28 may be e ective in reducing intestinal and systemic acute inflammation, specifically in mice.